2022
DOI: 10.3390/nu14153022
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 and mTORC2 Complexes Regulate the Untargeted Metabolomics and Amino Acid Metabolites Profile through Mitochondrial Bioenergetic Functions in Pancreatic Beta Cells

Abstract: Background: Pancreatic beta cells regulate bioenergetics efficiency and secret insulin in response to glucose and nutrient availability. The mechanistic Target of Rapamycin (mTOR) network orchestrates pancreatic progenitor cell growth and metabolism by nucleating two complexes, mTORC1 and mTORC2. Objective: To determine the impact of mTORC1/mTORC2 inhibition on amino acid metabolism in mouse pancreatic beta cells (Beta-TC-6 cells, ATCC-CRL-11506) using high-resolution metabolomics (HRM) and live-mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…We have previously shown that inhibition of the mTORC1 nutrient-sensing complex by Rapamycin and mTORC1/mTORC2 inhibition via either Torin-2 or RapaLink-1 have differential effects on the global untargeted metabolomics in vitro cell culture models [3]. In this proof-of-concept study, we leveraged the mummichog Python algorithm to analyze the high-dimension untargeted metabolomics data for modeling the biochemical pathways and metabolic networks, and predicting their functional activity using the XCMS Plus bioinformatics platform [4,5].…”
Section: Objectivesmentioning
confidence: 99%
“…We have previously shown that inhibition of the mTORC1 nutrient-sensing complex by Rapamycin and mTORC1/mTORC2 inhibition via either Torin-2 or RapaLink-1 have differential effects on the global untargeted metabolomics in vitro cell culture models [3]. In this proof-of-concept study, we leveraged the mummichog Python algorithm to analyze the high-dimension untargeted metabolomics data for modeling the biochemical pathways and metabolic networks, and predicting their functional activity using the XCMS Plus bioinformatics platform [4,5].…”
Section: Objectivesmentioning
confidence: 99%